2015
DOI: 10.3766/jaaa.14094
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Effects of Dichotic Attentional Mode on Interaural Asymmetry: An AERP Study with Independent Component Analysis

Abstract: IA differences between YAs and MAs were revealed in the N400 only in DIV, which was the result of an increased information-processing load. ICA successfully separated temporally overlapping EEG sources that contributed to the N400 component, allowing a refined interpretation of differences in the AERP waveform among groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Note that in the current study, participants presented with worse hearing thresholds in the LE than the RE despite showing no significant difference between ears (Table 2). Consistent with Dorman et al (1985), poorer auditory thresholds, even in the presence of normal age-appropriate hearing, is associated with older adults’ difficulties to process spectrotemporal acoustic cues to identify stop consonant syllables. In addition, CV-syllables minimize the relevance of cognitive-control processes and lexical component (i.e., internal redundancy) in DL tasks as opposed to digits and sentences which provide more lexical information (Findlen & Roup 2011).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Note that in the current study, participants presented with worse hearing thresholds in the LE than the RE despite showing no significant difference between ears (Table 2). Consistent with Dorman et al (1985), poorer auditory thresholds, even in the presence of normal age-appropriate hearing, is associated with older adults’ difficulties to process spectrotemporal acoustic cues to identify stop consonant syllables. In addition, CV-syllables minimize the relevance of cognitive-control processes and lexical component (i.e., internal redundancy) in DL tasks as opposed to digits and sentences which provide more lexical information (Findlen & Roup 2011).…”
Section: Discussionmentioning
confidence: 63%
“…It has also been suggested that a greater LE deficit among older adults may be linked to age-related declines in cognitive functions (Davis et al 2015). Hällgren et al (2001) showed that working memory and speed of processing were significantly associated with DL when subjects had to selectively attend to the LE stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of aging on dichotic listening tests has already been reported by several authors (3,4,20) , even when there is no great variation in an age group or when in young population, it is possible to observe differences between the performance of younger and older individuals, where young people obtained better results (3,4,20) . This fact stems from the structural and morphological changes arising from the aging process (19) and the reduction of other capacities related to superior mental functions such as memory, language, planning and sequence capacity (21,22) .…”
Section: Resultsmentioning
confidence: 99%
“…There are several objective and subjective behavioral and physiological measures sensitive to the amount of effort required for listening [58]. Delayed recall [23,76], dual-task procedures [56], perceived effort [25,55], ERPs [27,49,50] and cardiac measures63 have been used as indicators of listening effort.…”
Section: Speech-in-noise (Sin) Listening Effortmentioning
confidence: 99%